2020
DOI: 10.1186/s12891-020-03202-8
|View full text |Cite
|
Sign up to set email alerts
|

RaceRunning training improves stamina and promotes skeletal muscle hypertrophy in young individuals with cerebral palsy

Abstract: Background: Individuals with cerebral palsy (CP) are less physically active, spend more time sedentary and have lower cardiorespiratory endurance as compared to typically developed individuals. RaceRunning enables highintensity exercise in individuals with CP with limited or no walking ability, using a three-wheeled running bike with a saddle and a chest plate for support, but no pedals. Training adaptations using this type of exercise are unknown. Methods: Fifteen adolescents/young adults (mean age 16, range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…The results of the current survey showed that most participants thought that Frame Running enabled them to exert themselves physically, which supports observations from previous studies ( 15 , 16 ). This potential of Frame Running to enable moderate-to-vigorous physical activity and thereby improve cardiovascular fitness is important, as this level of physical exertion is difficult to achieve during other sports for many individuals with severe mobility impairments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the current survey showed that most participants thought that Frame Running enabled them to exert themselves physically, which supports observations from previous studies ( 15 , 16 ). This potential of Frame Running to enable moderate-to-vigorous physical activity and thereby improve cardiovascular fitness is important, as this level of physical exertion is difficult to achieve during other sports for many individuals with severe mobility impairments.…”
Section: Discussionsupporting
confidence: 91%
“…Bolster et al ( 15 ) found that adolescents who are moderately-to-severely affected by CP can reach a close-to-maximum heart rate (> 180 bpm) during the 6-min Frame Running test. Similar high-intensity exercise levels (mean heart rate > 65% of age-related maximum heart rate during training) in young people with CP were shown in a 12-week Frame Running training intervention by Hjalmarsson et al ( 16 ). This study also demonstrated improved cardiorespiratory endurance and hypertrophy of the gastrocnemius.…”
supporting
confidence: 68%
“…Our study was set to begin in the winter of 2020. Consistent with previous studies by other investigators (Hjalmarsson et al, 2020), the initial strategy was to have all sessions conducted in person after school. However, fully remote school education for much of the 2020-2021 school year meant that an alternative strategy was required (Egan et al, 2021).…”
Section: Methodsmentioning
confidence: 93%
“…The RPE is based on the sensations felt during exercise, such as muscle fatigue, increased heart rate, and increased breathing ( Andrews et al, 2013 ). The RPE, although subjective, is used in several studies with the CP population ( Maltais et al, 2004 ; Maanum et al, 2010 ; Runciman et al, 2016 ; Hjalmarsson et al, 2020 ) and can be considered a valuable indicator to monitor the tolerance to exercise and signalize imminent fatigue (ACSM).…”
Section: Methodsmentioning
confidence: 99%